Pemberdayaan Ekonomi Berbasis Penyusunan Laporan dan Tata Kelola Keuangan Usahatani Pada Kelompok Tani di Desa Ayula Selatan Kecamatan Bulango Selatan Kabupaten Bone Bolango: Pengabdian - Mohammad Zubair Hippy; ST. Aisyah R.; Muhammad Rizq Gobel; Siti Rahmatia Machieu (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This community service program aims to enhance the capacity and economic empowerment of farmers through training in the preparation of financial reports and farm financial management in Ayula Selatan Village, Bulango Selatan District, Bone Bolango Regency. The main issues faced by farmers in this area are the low level of understanding regarding farm financial recordkeeping and the suboptimal financial management practices, which affect both cost efficiency and income effectiveness. The program was implemented in three stages: the preparation stage, which included problem identification, determination of time and participants, and formulation of an implementation agreement; the implementation stage, which involved socialization, technical guidance, and hands-on training in financial recording and reporting; and the evaluation stage, conducted through pre-test and post-test assessments. The evaluation results showed significant improvement in three key aspects. In terms of credit assessment understanding, the score increased from 51.87% to 63.80%. Understanding of financial reporting also improved, with scores rising from 45.44% to 61.56%. Meanwhile, income effectiveness and cost efficiency improved from 60.17% to 77.33%.